Asymptotic Exponential Arbitrage in a Liu-Tang 3-Factor Model of Commodity Futures (African Journal for Industrial and Applied Mathematics, 2025)
From a 3-factor model of storable commodities discussed by Liu andTang (2010), we consider a cash market model such as futures exchange with a single futures contract on one such commodities and a money market account. Afterverifying that this model is arbitrage-free and incomplete in any finite time horizonor delivery date, we show that there still exists a possibility to generate exponentially growth risk-less profit in long term; a form of asymptotic arbitrage conjectured by Föllmer and Schachermayer (2008) and first solved by Mbele Bidima andRásonyi (2012) in financial security models. And we find that works in this paper generalize our recent works in Tadesse Welemical et al. (2019) on Schwartz’sone-factor model of commodity futures.
Keywords: Asymptotic exponential arbitrage; commodity market; futures contract; large deviation.